Physical and Mechanical Properties of Deep Oceanic Sediments Cored from the Bottom of Challenger Deep, Mariana Trench - Xu Dai; Tao Xu; Jian Chen (Geofluids)
The deep oceanic sediments were collected from the Challenger Deep in the southwestern part of the Mariana Trench. Considering the salt in the pore water, a modified method for determining the physical and mechanical properties of the deep-sea sediments was proposed, by which the geological engineering indices were measured and corrected. Through the scanning electronic microscope (SEM), the microstructures of the sediments were found to be composed of flocculation, with a large number of diatom debris and empty shells of organism around it. As a consequence, the porosity and compressibility are high; internal friction angle and cohesion are low. Besides high water content, high porosity, high liquid limit, high plasticity, high consolidation coefficient, low compressive modulus, low shear strength, low density, and low specific gravity, the deep-sea mining machine may slip and subside. This research can improve the understanding of the deep-sea sedimentary environment of the Challenger Deep in the southwestern part of the Mariana Trench and provide an essential reference for the parameter calibration as well as the basis for walking-characteristic study and optimization design of the deep-sea mining vehicle.